Clinicopathological Changes in Adjuvant Induced Arthritis in Canine Stifle Joint - Ismail, Siti Norhayati (2001)
Osteoarthritis is the most common joint disease ,and cause of physical disability in man and animals. It is a complex disease with unknown etiology. Intra-articular injection of 1 ml. Freund's adjuvant was inoculated into twenty-five adult Mongrel dogs weighing between 10-15kg. Osteoarthritis was induced in the left stifle joint, while the right joint act as a control. The dogs were evaluated for clinical evidence of joint heat, effusion and pain, and gait abnormalities. Radiographs were obtained for soft tissue swelling, osteophytosis and degenerative changes. At the end of each trial period (week 1, 2, 3, 4, 5) the dogs were euthanised. The left stifle joint were opened, examined grossly and the articular cartilage and synovial membrane were harvested and fixed for histopathologic and electron microscopic studies. Clinical signs of joint swelling and pain upon palpation, weight bearing lameness and reduced range of motion were observed within week 1 post-inoculation. These signs were positively correlated with the acute pathological lesions in the synovial membrane and articular cartilage; and in radiograph evaluation. Radiograph study revealed evidences of soft tissue swelling, increased intra-articular space, osteophytes formation; the clinical signs that were suggestive of degenerative changes in osteoarthritis. However, plain radiograph was found to be not informative enough in the early stage of osteoarthritis. Gross changes during post mortem revealed, swelling of the adjacent soft tissue, hypertrophy of the joint capsule and synovial membrane, and joint effusion. These were signs of inflammation of the joint tissues and it was believed that the inflammatory process was one of the major factors in the development of degenerative joint disease. Lameness evaluation was positively correlated with gross examination but negatively correlated with radiograph examination. In histopathology study, there were signs of inflammation in the synovial membrane and formation of synovial pannus, which was thought to be related with the development of degenerative changes on the articular cartilage. Hyperplasia of intima and subintima layer, edema and congestion; flaking and erosion in articular cartilage, were observed as early as week 1 p.i. Under scanning electron microscopy, cartilage fibrillation and erosion, were observed as early as week 1 p.i. Significant positive correlation between the histological changes in articular cartilage with changes in the synovial membrane suggested that changes in the synovium preceded changes in the articular cartilage. The synovial membrane was highly vascularised, causes respond to injury more promptly. In articular cartilage, it took time to heal since healing depending on the depth of lesion. In this study, the pathogenesis of osteoarthritis was divided into three stages: the onset phase, which was observed within one week post-induction; the second phase or the intermediate stage and the end phase. Each structure, cells and tissues was found to have their own role in the production of osteoarthritis . Study on the pathogenesis must emphasize on these structures and cascade of events that occur during the production of osteoarthritis, which will aid in the treatment of osteoarthritis. The clinical, morphological and microstructure changes that occurred in osteoarthritis had been characterised , but the role of each in the aetio-pathogenesis of osteoarthritis, is still not rigidly defined.